Enhancing inclusive growth to create new evidence of rural diversity: an analysis in the Highlands and Islands of Scotland - Jonathan Hopkins; Margaret Currie; Nicholas Schurch; Graciela Martínez-Sánchez; Valentina Farinelli (Regional Studies, Regional Science)
This article applies a modified perspective of inclusive growth in order to understand the diversity of communities within a remote and predominantly rural region of northern Europe. A transdisciplinary process co-constructed an enhanced and regionally appropriate framework of inclusive growth, which recognised the importance of evaluating the concept as multidimensional and affected by the uneven contexts of physical geography and connectivity, and social characteristics, which influence development potential and community resilience, and which extend the relevance of inclusive growth to rural places. Operationalisation of this framework was achieved at the local level through quantitative multivariate analysis, which identified underlying dimensions of inclusive growth ‘performance’ representing interactions of broad economic outcomes and variation in geographical and social contexts, and then clusters of locations with similar characteristics. The evidence of multidimensional and geographical inequalities from this analysis was evaluated using a spatial justice perspective, enhancing the applicability of an inclusive growth framing as a means of understanding the wellbeing economy and rural diversity. Conceptually, the regionally-sensitive understanding of inclusive growth performance builds on and develops existing broader framings of inclusive growth. To avoid leaving places behind, policies which seek to achieve inclusive growth should recognise and adapt to nuanced and localised inequalities.